Natural convection and melting of NEPCM in a corrugated cavity under the effect of magnetic field - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Springer, 2020)
Numerical study of natural convection and melting in a corrugated square cavity filled with CNT-water nanofluid under the influence of inclined magnetic field was performed. The left and right walls of the cavity are kept at constant temperatures while the horizontal wall is adiabatic. Galerkin weighted residual finite element was used. The effects of Hartmann number (between 0 and 40), magnetic inclination angle (between 0 degrees and 90 degrees), nanoparticle volume fraction (between 0 and 4%), number (between 1 and 20) and height (between 0.002 H and 0.16 H) of the corrugation on the convective heat transfer features and melting in the square cavity were examined. Magnetic field was found to dampen the fluid motion, and less movement of the melt front in the upper part of the cavity is observed. By using the CNT nanoparticles in the base fluid, significant enhancement in the heat transfer and faster propagation of the melt front is observed in the absence and presence of magnetic field. Average heat transfer enhancements are around 118% and 95% when nanofluid at the highest particle volume fraction is compared with water in the absence and presence of magnetic field. The heat transfer is reduced and melt front curve characteristics are affected when the number and height of corrugation waves are increased.
Keywords: Magnetohydrodynamic; PCM; Finite element method; Corrugation; CNT-water nanofluid